AZA HOLMES’S OBSESSIVE COMPULSIVE DISORDER IN JOHN GREEN’S TURTLES ALL THE WAY DOWN - Atmaja, Yodik Satriya; Wahyono, Danu (TANDA, 2024)
This research examines Aza Holmes’s Obsessive-Compulsive Disorder in John Green’s Turtles All the Way Down. It identifies manifestations of OCD through Aza's intrusive thoughts and repetitive behaviors, which are deeply rooted in her childhood habits. The research aims to achieve three objectives: to identify and describe of OCD in Aza's character, to examine its causes, and to analyze its effects. The scope of this study limits to Freud's psychoanalytic lens and focuses on a textual analysis of OCD main character in the novel. The significance of this study is to  offer insight into the complexities of OCD. Descriptive qualitative research design is used to involve gathering and analyzing data that are not numerical, but describes data related to the research topic. The study uses Sigmund Freud's theory of psychoanalysis, specifically the concepts of id, ego, and superego. The findings reveal that Aza’s OCD is triggers by both internal conflicts and external stimuli, such as her fixation on contamination and habitual self-injury. Her compulsions, such as repeatedly reopens wounds and drinking antiseptics, highlight the debilitating nature of the disorder. The study underscores how OCD affects her ability to maintain social connections, navigate personal relationships, and sustain her self-concept understanding in coping with OCD. This research contributes to the discourse on mental health representation in literature and demonstrates the value of psychoanalytic approach in unpacking complex characterization. It provides a foundation for future studies on the intersection of mental health and literary analysis, enriching both academic and practical perspectives on OCD.